Somatostatin Receptor Expression in the Thyroid Demonstrated with 111In-Octreotide Scintigraphy - Becker, W.; Schrell, U.; Buchfelder, M.; Hensen, J.; Wendler, J.; Gramatzki, M.; Wolf, F. (Nuklearmedizin - NuclearMedicine, 1995)
Neuroendocrine tumors with somatostatin receptor expression may be localized by 111ln-octreotide scintigraphy. This study examines those thyroid conditions where 111 ln-octreotide uptake could be observed also in the thyroid gland. 26 consecutive patients who underwent 111 ln-octreotide scintigraphy for tumor localization were additionally examined for thyroid disease by sonography and 99mTc-pertechnetate scintigraphy. 12 of these patients had no significant thyroid uptake and had an euthyroid normal-sized thyroid gland. 14 patiens with 111ln thyroid uptakes had endemic goiters, two of them with thyroid autonomy and one with Graves’ disease. Thus, 111 ln-octreotide thyroid uptake was predominantly seen in patients with endemic goiter with or without thyroid autonomy.Neuroendokrine Tumoren können szintigraphisch mit dem Somatostatinanalogon 111 In-Octreotid lokalisiert werden. Diese Studie untersucht verschiedene Schilddrüsenerkrankungen, bei denen ebenfalls ein 111 In-Octreotid-Uptake beobachtet werden konnte. 26 Patienten bei denen ein 111ln-Octreotid-Szintigramm aufgenommen worden war, wurden zusätzlich einer eingehenden Schilddrüsendiagnostik mit Sonographie und quantitativ ausgewertetem Schilddrüsenszintigramm unterzogen. 12 dieser Patienten zeigten einen vernachlässigbaren 1111n-Schild-drüsenuptake und hatten euthyreote und normal große Schilddrüsen. 14 Patienten mit einem erkennbaren 111ln-Uptake hatten eine endemische Struma, davon 2 Patienten eine zusätzliche Schilddrüsenautonomie und eine Patientin eine floride Immunhyperthyreose.
Keywords: 1llln-octreotide; thyroid uptake; iodine deficiency